2018
DOI: 10.1177/0271121417748197
|View full text |Cite
|
Sign up to set email alerts
|

Building Evidence in Early Childhood Special Education: A Systematic Review of Replication Intervention Studies

Abstract: Valid and evidence-informed practices are critical to help young children with disabilities and their families with highly effective interventions and instruction to reach their potentials. Replication research is critical for appraising research and identifying evidence-based practices. The purpose of this study was to replicate the methods used by Cook and colleagues and conduct a systematic review of the quantity, type, and findings of replication research in early childhood special education (ECSE). An int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 35 publications
0
4
1
Order By: Relevance
“…We identified 80 intervention studies on topics related to self-determination, of which 31 studies (39%) were identified as replications. This rate is slightly higher than that reported by Cook and colleagues (31%) in noncategorical special education research, but lower than the rate of replication reported by Banerjee, Movahedazarhouligh, Millen, and Luckner (2018) in early childhood special education intervention research (56%). Four studies were coded as direct replications and the remaining 27 studies were coded as conceptual replications.…”
Section: Discussioncontrasting
confidence: 65%
“…We identified 80 intervention studies on topics related to self-determination, of which 31 studies (39%) were identified as replications. This rate is slightly higher than that reported by Cook and colleagues (31%) in noncategorical special education research, but lower than the rate of replication reported by Banerjee, Movahedazarhouligh, Millen, and Luckner (2018) in early childhood special education intervention research (56%). Four studies were coded as direct replications and the remaining 27 studies were coded as conceptual replications.…”
Section: Discussioncontrasting
confidence: 65%
“…Replication is a particularly critical aspect of intervention research, as criteria for evidence-based practices typically require multiple studies (What Works Clearinghouse, Institute of Education Sciences, U.S. Department of Education, 2017). Furthermore, replications extend knowledge beyond just reproducing findings to establish evidence-based practices or uncover idiosyncratic, nuanced, or false findings (Banerjee, Movahedazarhouligh, Millen, & Luckner, 2018; Lemons et al, 2016; Makel et al, 2016). Systematic replications also identify new phenomena, which ensure comprehensive and balanced information is available to guide future research and practice (B.…”
mentioning
confidence: 99%
“…Despite the growing use of big data, much of the published research related to IDD relies on relatively small samples of convenience that may not be representative of the population, thereby producing results that may be difficult to replicate. Replicability failures in psychology and other life sciences are of considerable concern and have drawn recent attention to how to set standards for when replication occurs and how to legitimately claim that replication has occurred (Banerjee et al, 2018;Hedges & Schauer, 2019).…”
Section: Methodological and Treatment Limitationsmentioning
confidence: 99%